PENGARUH ASIMETRI INFORMASI TERHADAP KONSERVATISMA AKUNTANSI (STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA) - darmajaya, lp4m ibi (Jurnal Manajemen dan Keuangan, 2011)
This study aims at testing empirically the effect of information asymmetry on accounting conservatism. Dependent variable in this research is accounting conservatism which is measured by using conservatism alternative measure, information asymmetry as independent variable with the proxy of bid-ask spread, whereas control variable is consisted of leverage and size (company size).Â The sample is taken by purposive sampling. Based on that criteria, samples gathered is 65 companies with 325 observations. The data used is secondary data including bid price data and ask price data, and also data from annual report of manufacturing companies listed in Indonesian Stock Exchange. Data source is Pusat Data Bisnis dan Ekonomi FEB UGM. Hypothesis testing is done by using multiple linear regression (Ordinary Least Square).The result shows that information asymmetry has no positive effect on accounting conservatism. This conclusion does not support the prediction of agency theory and signaling theory. This indicates that the model used is not proper because the model is built on the construct of information asymmetry on accounting conservatism. Keywords: Information asymmetry, accounting conservatism, agency theory and signaling theory.